Toward a radically embodied neuroscience of attachment and relationships - Beckes, Lane; IJzerman, Hans; Tops, Mattie (Frontiers in Human Neuroscience, 2015)
Attachment theory (Bowlby, 1969/1982) posits that internal working models are a foundational feature of human bonds. Radical embodied approaches suggest that cognition requires no computation or representation, favoring a cognition situated in a body in context with affordances for action (Barrett, 2011; Chemero, 2009; Wilson & Golonka, 2013). We explore whether embodied approaches to social soothing, interpersonal warmth, separation distress, and support seeking could replace representational constructs such as internal working models with a view of relationship cognition anchored in the resources afforded to the individual by their brain, body, and environment interacting. We review the neurobiological bases for social attachments and relationships and attempt to delineate how these systems overlap or don’t with more basic physiological systems in ways that support or contradict a radical embodied explanation. We suggest that many effects might be the result of the fact that relationship cognition depends on and emerges out of the action of neural systems that regulate several clearly physically grounded systems. For example, the neuropeptide oxytocin appears to be central to attachment and pair-bond behavior (Carter & Keverne, 2002) and is implicated in social thermoregulation, being necessary for maintaining a warm body temperature in rats (Kasahara et al., 2007) and humans (Beck et al., 1979). Finally, we discuss the most challenging issues around taking a radically embodied perspective on social relationships. We find the most crucial challenge in individual differences in support seeking and responses to social contact, which have long been thought to be a function of representational structures in the mind (e.g., Baldwin, 1995). Together we entertain the thought to explain such individual differences without mediating representations or computations ending with a discussion of how representational approaches might be integrated with embodied approaches.